ANALISIS DISTRIBUSI PENDAPATAN PETANI UBI KAYU POLA KEMITRAAN DAN BUKAN KEMITRAAN PADA PT. SARI PATI SEMUDUN JAYA DI DESA BUKIT BATU KECAMATAN SUNGAI KUNYIT KABUPATEN PONTIANAK - Juniardi, Wahyu; Kusrini, Novira; Suyatno, Adi (Fakultas Pertanian Universitas Tanjungpura, 2012)
The purpose of this study was to determine and compare the income of cassava farmers farming partnership with PT. Sari Pati Semudun Jaya farmers are not partnerships and determine the level of inequality of distribution farm family incomes partnerships PT. Sari Pati Semudun Jaya farmers are not partnerships. Determination of the location in the village of Bukit Batu District Sungai Kunyit intentionally because in the village of Bukit Batu cassava farmers are being assisted by PT. Sari Pati Semudun Jaya. The research method is a survey method. Variable costs consisted of revenue, income, and income distribution. The population in this study amounted to 56 households, 22 households farmer partnerships and 35 families of farmers is not a partnership. The sample size was determined by the Slovin method at fault 10% to a total of 36 samples taken, 14 samples farmer partnerships and 22 sample farmers are not partnerships. Analysis of the data used are revenue analysis, statistical t-test and analysis of Gini Ratio Test to determine the distribution of income. The average farm income of cassava farmers partnerships PT. Sari Pati Semudun Jaya Rp. 5,200,757, smaller than the average farm income of cassava farmers are not partnerships Rp. 7,215,092, Gini Ratio obtained from the analysis that the value of the Gini Ratio on cassava farmers partnerships is 0.1 or lower indicates inequality. Gini Ratio value of cassava farmers and not the partnership is 0.1 or lower indicates inequality. Keywords: Income, Cassava Farming, Income Distribution.